A case study Evaluation of the Application of Infection Prevention Bundles in Reducing Infection Risk Factors in Total Thyroidectomy Patients at IBS RSP Hasanuddin University of Makassar - Tendri Mariadjeng Nurpa Masahude; Takdir Tahir; Abdul Majid; Syahrul Ningrat (JURNAL KEPERAWATAN DAN FISIOTERAPI (JKF), 2025)
Background: Surgical area infections (IDOs) are a form of Healthcare Associated Infections (HAIs) that often occur, especially in complex surgical procedures such as total thyroidectomy, which has a high risk of infection due to the long duration of surgery and involvement of vital structures. Prevention of IDO can be done through the implementation of infection prevention bundles, including the administration of prophylactic antibiotics, pre and perioperative antiseptics, as well as blood temperature and glucose control. The purpose of the study is to evaluate the application of infection prevention bundles in reducing the risk of infection in patients undergoing total thyroidectomy with a diagnosis of bilateral thyroid cancer at the Central Surgical Installation of Hasanuddin University Hospital, Makassar. Methods: This study used a descriptive case study design with a single case design method on Mrs. M's patients through three phases: pre-operative, intra-operative, and post-operative. The implementation of the infection prevention bundle includes the administration of prophylactic antibiotics, sterility techniques, blood sugar control, body temperature monitoring, and systematic wound care. Results: The total risk score of perioperative infection was 14 out of 30, indicating a moderate-high risk. However, the implementation of infection prevention bundles has proven to be effective in preventing infection. Evaluation of wound healing using the Southampton Wound Assessment Scale showed that the patient's wound was in a normal healing condition with no signs of infection until the fifth postoperative day. The patient was discharged on the fifth day with good general condition, normal swallowing function, and closed wounds without complications. Conclusions and suggestions: Consistent application infection prevention bundles can lower the risk of surgical area infection, accelerate wound healing, and shorten the duration of hospitalization. This study recommends the management of pre-operative risk factors such as hypertension control and patient education about postoperative wound care for sustainable healing. of This case study examines the application of infection risk factors in total thyroidectomy patients. The risk score for perioperative infection is 14 out of 30, which indicates a moderate-high risk. However the implementation infection prevention bundles has proven to be effective in preventing infection. The administration of prophylactic antibiotics, sterility techniques, blood sugar control, body temperature monitoring, and systematics wound care.